Climatic and tectonic controls on Late Triassic to Middle Jurassic sedimentation in northeastern Guangdong Province, South China - Pang, C.; Li, Zheng-Xiang; Xu, Y.; Wen, S.; Krapež, B. (Elsevier BV, 2016)
Stratigraphic analyses document climatic and tectonic controls on the filling of a Late Triassic to early Middle Jurassic (T3–J2) basin that developed on top of a young orogenic belt in southeastern South China. About 2700 m of Carnian to Bajocian sedimentary rocks is documented in the Meizhou region, Guangdong Province. The Carnian to Rhaetian sequence is characterized by deltaic facies that are succeeded by Hettangian fluvial, shallow marine and volcaniclastic facies, and by Sinemurian to early Toarcian interdistributary bay and floodplain facies. The late Toarcian to Bajocian sequence comprises proximal alluvial to lacustrine facies that changed upwards to fluvial facies. Fossil assemblages indicate that climatic conditions changed from tropical/subtropical warm humid, to temperate humid, and then to hot arid through the Late Triassic to the Middle Jurassic. Climatically induced changes (e.g., in precipitation, vegetation and erosion) exerted a strong influence on sediment supply, whereas tectonics played a dominant role in stratigraphic evolution, accommodation generation, sedimentation pattern and volcanism. Tectonostratigraphic analysis shows that the T3–J2 basin was initiated on an orogenic belt during late-stage orogeny, and evolved into shallow-marine and volcanic environments and then back to terrestrial facies during the post-orogenic stage. This was followed by regional uplift and the development of a basin-and-range province. The order of these events is similar to that of the central Rocky Mountains, western North America during the Palaeogene. The Mesozoic basin of South China and the Eocene basins of the central Rocky Mountains highlight the importance of subduction-related subsidence above young and broad orogens.